A CRISE CAPITALISTA E O ENDIVIDAMENTO EXTERNO E PÚBLICO DO MARANHÃO E O EMPOBRECIMENTO SOCIAL - José Menezes Gomes (Universidade Federal do Maranhão, 2012)
This paper intends to analyze the external debt of Maranhão, since 1972, its conversion into public debt, making a connection between the crisis of overproduction in the early '70s and the expansion of a private international monetary system, called Euromarket of currencies, which had in the military regimes in Latin America a fertile field for their actions.